육계 유통단계별 가격과 변동성의 비대칭성 분석 - 임상수 (한국농촌경제연구원, 2012)
The retail price is increasing rapidly compared to farm price and wholesale price in the Korean chicken market. This paper focuses on that there are two reasons for this happening. The first one is the price and volatility asymmetry in the chicken marketing channel, and the second one is the avian influenza. There are 4 avian influenzas from 2000 in Korea. The GJR-GARCH model is used to test it. Results show that there is asymmetry in the speed of retail price and in the sum of retail price adjustments to wholesale price. But wholesale price responds similarly to farm price change. This paper shows that the volatility of retail prices to wholesale prices is asymmetric. Finally, only the third and fourth avian influenza had influenced the positive effect on the retail price. So this paper concludes that price and volatility asymmetry and avian influenza make the retail price increase faster than farm price and wholesale price.
Keywords: 가격 비대칭성; 변동성 비대칭성; 일반화된 자기 회귀 조건부 이분산 모형; price asymmetry; volatility asymmetry; GARCH model; Generalized Autoregressive Conditional Heteroskedasticity model